Pottery excellent in beauty and antifouling properties
Patent Information
- Application Number
- JP2025003130
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-03-31
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-26
Smart Images

Figure 2025041991000005 
Figure 2025041991000006 
Figure 2025041991000007
Abstract
Description
[Technical field]
[0001] The present invention relates to pottery having a glaze layer, and more particularly to pottery having excellent appearance and stain resistance. [Background technology]
[0002] Recently, ceramics such as sanitary ware and tiles are required to have a high level of aesthetic appeal due to the growing demand for aesthetic spaces. Furthermore, with changes in the way toilet spaces are used, such as the use of smartphones, there are more opportunities for ceramics to be scratched, such as heavy objects being dropped on them.
[0003] For sanitary ware and ceramics used in wet areas, it is desirable to have superior properties in terms of hygiene, such as making it difficult for dirt to adhere and making it easy to remove any dirt that does adhere. In addition, due to improved awareness of hygiene and the COVID-19 pandemic, attention is being paid to invisible levels of dirt on ceramic surfaces.
[0004] In order to make it difficult for dirt to adhere to the glaze layer surface of pottery or to make it easy to remove the adhered dirt, the smoothness of the glaze layer surface is generally controlled to a high level. However, the physical shape of the glaze layer surface alone may not be enough to prevent adhesion. For example, in the case of viruses or fine dirt, the adhesion cannot be effectively prevented even if the surface is made smooth, and it cannot necessarily be said that the removal of the dirt is easy.
[0005] For example, Japanese Patent Laid-Open Publication No. 2001-123278 (Patent Document 1) proposes to control the electrical properties of the surface of pottery by improving the zeta potential and antibacterial properties of the glaze layer surface. Japanese Patent Laid-Open Publication No. 9-63379 (Patent Document 2) discloses control of the dielectric constant of ceramic sand and the relative dielectric constant of the glaze layer, but the purpose is to improve the dielectric breakdown strength of suspension insulators (insulating devices). Japanese Patent Laid-Open Publication No. 9-328380 (Patent Document 3) discloses a glazing method in which the concentration of the glaze is measured based on the electrical conductivity and the amount of glaze attached to the base is adjusted, but the properties of the finished glaze layer are not mentioned at all. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2001-123278 A [Patent Document 2] Japanese Patent Application Publication No. 9-63379 [Patent Document 3] Japanese Patent Application Publication No. 9-328380 Summary of the Invention [Problem to be solved by the invention]
[0007] The present inventors have now discovered that controlling the electrical properties of the surface of the glaze layer of pottery can improve the aesthetic appearance of the pottery and also suppress adhesion of fine dirt to the surface. Furthermore, the electrical properties of the glaze layer can be efficiently controlled by appropriately managing manufacturing conditions such as the preparation of the glaze raw materials and the conditions for applying them to the pottery body. The present invention is based on this discovery.
[0008] Therefore, an object of the present invention is to provide pottery that is excellent in appearance and stain resistance. [Means for solving the problem]
[0009] According to a first aspect, the pottery of the present invention is pottery comprising at least a pottery body and a glaze layer, and is characterized in that the relative dielectric constant of the surface of the glaze layer is greater than 5.5 and less than 6.0.
[0010] According to a second aspect, the pottery of the present invention is pottery comprising at least a pottery body and a glaze layer, and is characterized in that the dielectric tangent tan δ of the surface of the glaze layer is 0.0040 or more and 0.0065 or less.
[0011] According to a third aspect of the present invention, the pottery comprises at least a pottery body and a glaze layer, and the surface resistivity of the surface of the glaze layer is 4.0×10 14 Ω or more 8.0×10 14 It is characterized in that the resistance is Ω or less. Effect of the Invention
[0012] The ceramic according to the present invention can improve the aesthetic appearance and suppress the adhesion of fine dirt to the surface. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a schematic diagram of a glaze sample with electrodes attached for measuring the relative dielectric constant of the glaze layer. [Diagram 2] FIG. 2 is a schematic diagram of a glaze sample with electrodes attached for measuring the surface resistivity of the glaze layer. [Diagram 3] 1 is an image taken by a digital microscope of the surface of the glaze layer of Example 1 after acetylene carbon black was adhered to the glaze layer and the glaze layer was left to stand for 30 minutes in an atmosphere with a wind speed of 1.0 m / s. [Figure 4] 1 is an image of the surface of the glaze layer of Comparative Example 1 photographed with a digital microscope after an experiment in which acetylene carbon black was adhered to the glaze layer under the same conditions as in Example 1 above. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Pottery In the present invention, "ceramics" refers to sanitary ware, tiles, and other items that have a basic structure of a glaze layer on a ceramic base. In addition, "sanitary ware" refers to ceramic products used in bathrooms, toilet spaces, dressing rooms, washrooms, kitchens, etc. Specifically, it refers to toilet bowls, urinals, toilet basins, toilet tanks, wash basins, hand basins, etc.
[0015] glaze
[0016] In the present invention, the glaze may be a mixture of natural mineral particles such as silica sand, feldspar, and limestone, and / or an amorphous glaze, to which an opacifier and a pigment are further added. Examples of opacifiers include zircon and tin oxide. The composition of the glaze is, for example, 52 to 80 parts by weight of SiO2, 5 to 14 parts by weight of Al2O3, 6 to 17 parts by weight of CaO, 0.5 to 4.0 parts by weight of MgO, 0.1 to 11 parts by weight of ZnO, 1 to 5 parts by weight of K2O, 0.5 to 2.5 parts by weight of Na2O, 0.1 to 15 parts by weight of opacifier, and 0.001 to 20 parts by weight of pigment. The glaze may further contain a paste, a dispersant, a preservative, an antibacterial agent, and the like. Examples of pigments include cobalt compounds and iron compounds. The amorphous glaze refers to a glaze obtained by melting a glaze raw material consisting of a mixture of the above-mentioned natural mineral particles at a high temperature and vitrifying it. For example, a frit glaze can be suitably used.
[0017] First aspect of the present invention The ceramic according to the first aspect of the present invention has a relative dielectric constant of the surface of the glaze layer exceeding 5.5 and less than 6.0. By using such a glaze layer, the ceramic has excellent appearance and can suppress adhesion of fine dirt to its surface. Here, fine dirt means a particle size that cannot be effectively or easily prevented from adhering only by the physical shape of the glaze layer surface, for example, a particle size of about 300 nm from the virus level. The ceramic according to the present invention has excellent appearance, particularly improved luster and color development, and also has the property of preventing the adhesion of fine dirt or easily removing fine dirt that has already adhered. Therefore, for example, by using the ceramic according to the present invention on the entire surface of the area visible to the user or the area where dirt is likely to adhere, a sanitary ceramic including a toilet and a urinal that has excellent appearance and is difficult to stain can be obtained.
[0018] Here, the relative dielectric constant of the glaze layer of pottery can be measured in accordance with JIS C2138. Specifically, it is measured by the following method. First, a pottery test piece having a glaze surface is prepared. The test piece may be prepared for testing under the same conditions as the product, such as the glaze composition, base composition, and firing temperature, or may be cut out from the pottery product while maintaining the surface. Here, the thickness of the test piece is 1 mm. This test piece may be 1 mm including the base in addition to the glaze layer. Next, as shown in FIG. 1, the main electrode 11 and the counter electrode 12 are attached to the test piece 10. Here, the main electrode 11 and the counter electrode 12 are disc electrodes without a guard ring, the main electrode 11 and the counter electrode 12 have different diameters, and the thickness a of the main electrode 11 is sufficiently smaller than the thickness h of the test piece. In addition, the main electrode 11 and the counter electrode 12 are made of Ag, and an Ag layer is formed by Ag paste or ion sputtering. The capacitance between the electrodes of the test piece is then measured using an impedance analyzer, and the relative dielectric constant is calculated using the following formula: The measurement conditions are in the air, at room temperature, and at a frequency of 1 MHz.
number
[0019] Furthermore, according to a first aspect of the present invention, there is provided a method for evaluating the surface aesthetics or stain resistance of pottery, which is characterized by preparing pottery with a glaze layer, measuring and calculating the relative dielectric constant of the surface of the glaze layer, and preferably includes a step of evaluating the surface aesthetics or stain resistance of the pottery as excellent when the relative dielectric constant of the surface of the glaze layer is more than 5.5 and less than 6.0. According to the method of the present invention, it is not limited to the evaluation of actual pottery, but for example, by preparing a test piece and measuring its electrical properties, it is possible to evaluate the surface aesthetics or stain resistance of the final product, which has the advantage of allowing the composition of the glaze, firing conditions, etc. to be set efficiently, thereby improving production efficiency.
[0020] Second Aspect of the Invention The ceramic according to the second aspect of the present invention has a dielectric tangent tanδ of the surface of the glaze layer of 0.0040 or more and 0.0065 or less. By using such a glaze layer, the ceramic has excellent appearance and can suppress the adhesion of fine dirt to its surface. Here, the fine dirt means a particle size that cannot be effectively or easily prevented from adhering only by the physical shape of the glaze layer surface, for example, a particle size of about 300 nm from the virus level. The ceramic according to the present invention has excellent appearance, particularly improved luster and color development, and also has the property of preventing the adhesion of fine dirt or easily removing fine dirt that has already adhered. Therefore, for example, by using the ceramic according to the present invention on the entire surface of the area visible to the user or the area where dirt is likely to adhere, a sanitary ceramic including a toilet and a urinal that has excellent appearance and is difficult to stain can be obtained.
[0021] Here, the dielectric tangent tanδ of the glaze layer of the pottery can be measured in accordance with JIS C2141. Specifically, in the same manner as in the first embodiment, a test piece is prepared, electrodes are formed on it, and the impedance is measured by an impedance analyzer. That is, the test piece may be prepared for testing under the same conditions as the product, such as the glaze composition, base composition, and firing temperature, or may be cut out from the pottery product while maintaining the surface. Here, the thickness of the test piece is 1 mm. This test piece may be 1 mm including the base in addition to the glaze layer. Next, as shown in FIG. 1, the main electrode 11 and the counter electrode 12 are attached to the test piece 10. Here, the main electrode 11 and the counter electrode 12 are disc electrodes without a guard ring, the main electrode 11 and the counter electrode 12 have different diameters, and the thickness a of the main electrode 11 is sufficiently smaller than the thickness h of the test piece. In addition, the main electrode 11 and the counter electrode 12 are made of Ag, and the Ag layer is formed by Ag paste or ion sputtering. The dielectric tangent tanδ is then measured using an impedance analyzer under the following measurement conditions: in air, at room temperature, and at a frequency of 1 MHz.
[0022] Furthermore, according to a second aspect of the present invention, there is provided a method for evaluating the surface aesthetics or stain resistance of pottery, which is characterized by preparing pottery with a glaze layer, measuring and calculating the dielectric loss tangent tanδ of the surface of the glaze layer, and preferably includes a step of evaluating the surface aesthetics or stain resistance of the pottery as excellent when the relative dielectric constant of the surface of the glaze layer is 0.0040 or more and 0.0065 or less. The method according to the present invention is not limited to the evaluation of actual pottery, but can also provide the advantage that the surface aesthetics or stain resistance of the final product can be evaluated by, for example, preparing a test piece and measuring its electrical properties, thereby efficiently setting the composition of the glaze, firing conditions, etc., and improving production efficiency.
[0023] Third aspect of the present invention The ceramic according to the third aspect of the present invention has a surface resistivity of the surface of the glaze layer of 4.0×10 14 Ω or more 8.0×10 14Ω or less. By using such a glaze layer, the pottery has excellent appearance and can suppress the adhesion of fine dirt to its surface. Here, fine dirt means a particle size that cannot be effectively or easily prevented from adhering only by the physical shape of the glaze layer surface, for example, a size of about 300 nm from the virus level. The pottery according to the present invention has excellent appearance, particularly improved luster and color development, and also has the property of preventing the adhesion of fine dirt or easily removing fine dirt that has already adhered. Therefore, for example, by using the pottery according to the present invention on the entire surface of the area visible to the user or the area where dirt is likely to adhere, a sanitary pottery including a toilet and a urinal that has excellent appearance and is difficult to stain can be obtained.
[0024] Here, the surface resistivity of the glaze layer of pottery can be measured in accordance with JIS C2141. Specifically, it is measured by the following method. First, a pottery test piece with a glaze surface is prepared. The test piece may be prepared for testing under the same conditions as the product, such as the glaze composition, base composition, and firing temperature, or may be cut out from the pottery product while maintaining the surface. Here, the thickness of the test piece is 1 mm. This test piece may be 1 mm including the base in addition to the glaze layer. Next, as shown in FIG. 2, a main electrode 21, a guard electrode 22, and a counter electrode 23 are attached to the test piece 20. These electrodes are made of Ag, and an Ag layer is formed by Ag paste or ion sputtering. A DC voltage V (V) is applied to the sample piece, and the current I (mA) after charging for 1 minute is measured to determine the surface resistance R of the sample piece. S The surface resistivity ρ is calculated by measuring the surface resistivity ρ in the air at room temperature and at an applied voltage of 1000V.
number
[0025] Furthermore, according to a third aspect of the present invention, there is provided a method for evaluating the surface aesthetics or stain resistance of pottery, which is characterized by preparing pottery with a glaze layer, measuring and calculating the surface resistivity of the surface of the glaze layer, and preferably includes a step of evaluating the surface aesthetics or stain resistance of the pottery as excellent when the relative dielectric constant of the surface of the glaze layer is 4.0 or more and 8.0 or less. According to the method of the present invention, it is not limited to the evaluation of actual pottery, but for example, by preparing a test piece and measuring its electrical properties, it is possible to evaluate the surface aesthetics or stain resistance of the final product, which has the advantage of allowing the composition of the glaze, firing conditions, etc. to be set efficiently, thereby improving production efficiency.
[0026] Favourable properties of the glaze layer The surface of the glaze layer of the pottery according to the present invention preferably has the following L*a*b* values: L* is 81 to 94, a* is -0.4 to -0.1, and b* is 0.5 to 1.8. By combining with the above-mentioned requirements of the present invention, the pottery has excellent aesthetics, especially good color appearance.
[0027] Ceramic base In the present invention, the pottery body may be prepared from any desired raw material, for example, it can be obtained by preparing a body slurry from raw materials such as silica sand, feldspar, limestone, clay, etc., molding this, and firing it.
[0028] According to a preferred embodiment of the present invention, the pottery body contains, as the overall chemical composition at the time of firing, SiO2: 50-75wt%, Al2O3: 17-40wt%, and K2O+Na2O: 1-10wt%. In addition, it is preferable that the glass phase is 25-70wt%, and the crystal phase is 75-30wt%. The chemical composition of the main components constituting the glass phase is preferably SiO2: 50-80wt%, Al2O3: 10-40wt%, and K2O+Na2O: 4-12wt%, with the entire glass phase being taken as 100%. The mineral composition of the main components constituting the crystal phase is preferably α-alumina 0-60wt%, quartz 0-20wt%, and mullite 2-20wt%, with the entire body being taken as 100%. The mineral composition of the main components constituting the crystal phase may be a body material (for example, a vitreous body) that does not contain α-alumina. It is preferred that the SiO2 / Al2O3 ratio in the substrate is greater than 1.
[0029] How pottery is made Pottery according to the present invention may be produced by providing a pottery body, applying a glaze slurry thereto, and firing.
[0030] The glaze slurry can be obtained by pulverizing the glaze raw material with a ball mill or the like so that the 50% particle size of the glaze raw material is preferably 10 μm or less, more preferably 5 μm or less. In the glaze slurry, the particle size of the quartz raw material such as silica sand can be controlled separately from the other glaze raw materials to suppress the remaining quartz on the glaze surface.
[0031] According to a preferred embodiment of the present invention, pottery that satisfies the above requirements is efficiently manufactured by controlling the manufacturing conditions. First, the viscosity of the glaze slurry is set to 800 to 1200 mPa·s. This effectively prevents the precipitation and separation of the glaze slurry, and efficiently controls the electrical properties of the resulting glaze layer.
[0032] The application of the glaze slurry to the pottery body is preferably performed by spray coating under the following conditions: the pottery body is kept at 25-35°C during glazing, and the glaze water penetration time is set to 25-35 minutes. Furthermore, it is important to adjust the temperature of the glaze slurry during glazing to 25-30°C, regardless of the room temperature. In other words, temperature control here means controlling the temperature so as not to be affected by the atmospheric temperature that varies depending on the geographical or seasonal factors of the production site.
[0033] It is also preferable that drying after applying the glaze slurry to the pottery body is also performed under appropriate temperature control. For example, drying after application is performed for 2 hours or more in an atmosphere adjusted to 25 to 30°C. The pottery according to the present invention can be manufactured through sufficient moisture penetration and particle adhesion and fixation in the applied glaze.
[0034] The pottery according to the present invention may be produced by appropriately determining the firing conditions in consideration of the composition of the pottery body and the glaze. For example, after applying the glaze to the pottery body, the molded body may be sintered at a temperature of 800 to 1300°C to fix the glaze layer. EXAMPLES
[0035] The present invention will be further illustrated by the following examples, but the present invention is not limited to these examples.
[0036] Pottery manufacturing Preparing the glaze 2 kg of glaze raw materials consisting of the compositions of Examples 1 to 5 and Comparative Examples 1 to 4 in Table 1, 1 kg of water, and 4 kg of spheres were placed in a 6-liter ceramic pot, and crushed in a ball mill so that the particle size measurement results of the colored glaze slurry after crushing using a laser diffraction particle size distribution analyzer were 65% of particles less than 10 μm and the 50% average particle size (D50) was about 6.0 μm, to obtain glazes. For Examples 3 to 5 and Comparative Examples 1 and 3, silica sand that had been crushed separately in a ball mill to an average particle size of about 19 μm was mixed with other materials to obtain glazes. The viscosity of all the obtained glazes was 800 to 1200 mPa s.
[0037] [Table 1]
[0038] Applying the glaze to the pottery body As the pottery body, 38-75% by weight of sericite pottery stone and kaolin pottery stone as skeleton forming materials, 8-45% by weight of china clay (powder) and ball clay (powder) as plastic materials, 8-20% by weight of feldspar as main sintering aid, and 1-4% by weight of dolomite were weighed as raw materials so that the main composition was in the range of SiO2: 50-75wt%, Al2O3: 17-40wt%, and K2O+Na2O: 1-10wt%. Water and an appropriate amount of sodium silicate as a peptizer were added, and the mixture was wet-pulverized in a ball mill to obtain a pottery body material. The obtained pottery body material was molded by a slip casting molding method using a plaster mold to obtain a molded body, and the molded body was fired in an electric furnace to obtain a pottery body. The glazes of the above-mentioned examples and comparative examples were applied to the above by a spray coating method. Here, the pottery body was heated or cooled to a temperature of 25 to 35° C. as required, and the temperature of the glaze was also set to 25 to 35° C., and the glaze was spray-coated at an atmospheric temperature of 25 to 35° C. After glazing, the pottery was left to stand for 2 hours or more in an atmosphere adjusted to 25 to 30° C., and then fired under firing conditions of 1100 to 1300° C. for 2 to 25 hours to obtain pottery.
[0039] Calculating the relative dielectric constant The glazes of the above examples and comparative examples were applied to a ceramic base and fired under the same conditions as above to prepare glaze samples. These were cut into disks with a thickness of about 1 mm and a diameter of about 20 mm to prepare samples for measuring the relative dielectric constant. Electrodes were attached to these samples as shown in FIG. 1 in accordance with JIS C2138, and the capacitance between the electrodes was measured using an impedance analyzer (Impedance Analyzer E4990A, Keysight Technologies, Inc.), and the dielectric tangent was calculated using the above formulas (1) to (4). The measurement conditions were a frequency of 1 MHz, a temperature of room temperature, and an atmosphere of air, and the electrodes were formed by sputtering Ag. The results were as shown in Table 2 below.
[0040] Measurement of dielectric tangent tanδ Using the sample prepared for measuring the relative dielectric constant, electrodes were attached as shown in Figure 1, and the dielectric tangent tanδ between the electrodes was measured using an impedance analyzer. The measurement conditions were a frequency of 1 MHz, a temperature of room temperature, and an atmosphere of air, and the electrodes were formed by sputtering Ag. The results are shown in Table 2 below.
[0041] Calculating surface resistivity Using the sample prepared for measuring the relative dielectric constant, electrodes were attached as shown in FIG. 2 in accordance with JIS C2141, and the current after charging for 1 minute when a direct voltage current of 1000 V was applied to the sample was measured with a resistivity meter to obtain the surface resistance Rs. During the measurement, dry air was flowed in the atmosphere at 300 cc / min. The surface resistivity ρ was calculated from the obtained surface resistance Rs using the above-mentioned formulas (21) to (23). The results are shown in Table 2 below.
[0042] Evaluation of dirt adhesion prevention: residual fine particle amount (%) For tiles, 1.5g / cm 2After that, acetylene carbon black having a particle size of about 21 nm was attached to the sample with a load of 1.0 kg / cm2, and the sample was left to stand in an atmosphere with a wind speed of 1.0 m / s for 30 minutes. The surface was then photographed with a digital microscope, and the area ratio of the carbon black attached to the surface was calculated from the obtained images using image analysis software. Four images were taken for each sample, and the average area (%) calculated from the images was obtained. This was designated as the "amount of remaining fine particles present." The results are shown in Table 2. Furthermore, images of the surface photographed with a digital microscope in Example 1 and Comparative Example 1 are shown in Figs. 3 and 4.
[0043] Physical property evaluation test Measurement of the L*a*b* color system was performed using a spectrophotometer to obtain the L*, a*, and b* values. The obtained L*, a*, and b* values were as shown in Table 2.
[0044] Color evaluation The appearance of the obtained pottery was visually evaluated as follows: the color compared with the standard color was scored on a 5-point scale. The results are shown in Table 2.
[0045] [Table 2]
[0046] Preferred aspects of the present invention Preferred aspects of the present invention are as follows. Regarding the first aspect of the present invention, (1) Pottery having at least a base and a glaze layer, The sanitary ware, wherein the dielectric constant of the surface of the glaze layer is more than 5.5 and less than 6.0. (2) The pottery according to (1), wherein the L* of the surface of the glaze layer is 81 or more and 94 or less. (3) The pottery according to (1) or (2), wherein the a* of the surface of the glaze layer is -0.4 or more and -0.1 or less. (4) The pottery according to any one of (1) to (3), wherein the b* of the surface of the glaze layer is 0.5 or more and 1.8 or less. (5) The ceramic according to any one of (1) to (4), which is a sanitary ceramic. (6) A method for evaluating the surface aesthetics or stain resistance of ceramics, comprising the steps of: Prepare pottery with a glaze layer, The method comprises a step of measuring and calculating the relative dielectric constant of the surface of the glaze layer. (7) The method according to (6), in which the surface of the pottery is evaluated as having excellent aesthetic appearance or resistance to dirt adhesion when the relative dielectric constant of the surface of the glaze layer is greater than 5.5 and less than 6.0.
[0047] Regarding the second aspect of the present invention, (1) Pottery having at least a base and a glaze layer, The sanitary ware, wherein the dielectric tangent tanδ of the surface of the glaze layer is 0.0040 or more and 0.0065 or less. (2) The pottery according to (1), wherein the L* of the surface of the glaze layer is 81 or more and 94 or less. (3) The pottery according to (1) or (2), wherein the a* of the surface of the glaze layer is -0.4 or more and -0.1 or less. (4) The pottery according to any one of (1) to (3), wherein the b* of the surface of the glaze layer is 0.5 or more and 1.8 or less. (5) The ceramic according to any one of (1) to (4), which is a sanitary ceramic. (6) A method for evaluating the surface aesthetics or stain resistance of ceramics, comprising the steps of: Prepare pottery with a glaze layer, The method comprises a step of measuring and calculating the dielectric tangent tan δ of the surface of the glaze layer. (7) The method according to (6), in which the surface of the pottery is evaluated as having excellent aesthetic appearance or resistance to dirt adhesion when the dielectric tangent tan δ of the surface of the glaze layer is 0.0040 or more and 0.0065 or less.
[0048] Regarding the third aspect of the present invention, (1) Pottery having at least a base and a glaze layer, The surface resistivity of the surface of the glaze layer is 4.0×10 14 Ω or more 8.0×10 14 Sanitary ware, below Ω. (2) The pottery according to (1), wherein the L* of the surface of the glaze layer is 81 or more and 94 or less. (3) The pottery according to (1) or (2), wherein the a* of the surface of the glaze layer is -0.4 or more and -0.1 or less. (4) The pottery according to any one of (1) to (3), wherein the b* of the surface of the glaze layer is 0.5 or more and 1.8 or less. (5) The ceramic according to claim 1 or 2, which is sanitary ceramic. (6) A method for evaluating the surface aesthetics or stain resistance of ceramics, comprising the steps of: Prepare pottery with a glaze layer, The method comprises a step of measuring and calculating the surface resistivity of the surface of the glaze layer. (7) The surface resistivity of the surface of the glaze layer is 4.0 × 10 14 Ω or more 8.0×10 14 The method according to (6), wherein if the resistance is Ω or less, the surface of the pottery is evaluated as being excellent in aesthetic appearance or resistance to dirt adhesion.
Claims
1. A pottery having at least a base and a glaze layer, The sanitary ware, wherein the dielectric tangent tan δ of the surface of the glaze layer is 0.0040 or more and 0.0065 or less.
2. The pottery according to claim 1, wherein the L* of the surface of the glaze layer is 81 or more and 94 or less.
3. The pottery according to claim 1 or 2, wherein a* of the surface of the glaze layer is -0.4 or more and -0.1 or less.
4. The pottery according to claim 1 or 2, wherein the b* of the surface of the glaze layer is 0.5 or more and 1.8 or less.
5. 3. The ceramic according to claim 1 or 2, which is a sanitary ceramic.
6. A method for evaluating the surface aesthetics or stain resistance of ceramics, comprising the steps of: Prepare pottery with a glaze layer, The method comprises a step of measuring and calculating the dielectric tangent tan δ of the surface of the glaze layer.
7. The method according to claim 6, wherein the surface of the pottery is evaluated as being excellent in aesthetic appearance or stain resistance when the dielectric tangent tan δ of the surface of the glaze layer is 0.0040 or more and 0.0065 or less.
Citation Information
Patent Citations
Suspended insulator
JP1997063379A
Glazing of pottery and system therefor
JP1997328380A
Glazed product
JP2001123278A